Respons Akar Bibit Nanas MD2 Terhadap Pemberian ZPT IBA dan Sumber Bahan Tanam Berbeda : Response of MD2 Pineapple Seedling Roots to the Aplication of ZPT IBA and Different Planting Material Sources - Lestari, Datik; Krismiratsih, Fitri; Tri Cahyaningrum, Deltaningtyas; Mayasari, Financia (Politeknik Negeri Jember, 2025)
The aim of this research was to determine the effect of IBA concentration and the origin of planting material and their interactions on the rooting of MD2 pineapple seedlings. The research was carried out from August-October 2023 experimentally using a factorial Randomized Group Design (RAK). The first factor is the IBA concentration of 0 ppm, 200 ppm, 400 ppm, and 600 ppm and the second factor is crown shoots and tiller shoots. There are 8 treatment combinations each treatment is repeated 3 times so that there are 24 experimental units with 3 plant samples. The ANOVA results were tested further using the DNMRT test at the 5% level. The observation variables consisted of the number of primary roots and root volume of seedlings aged 30 DAP, length of primary roots and dry weight of roots of seedlings aged 100 HST. The research results showed that giving an IBA concentration of 400 ppm and seedling shoot planting material was the best treatment combination to produce good roots in MD2 pineapple seedlings.